Analysis of the village financial system (SISKEUDES) in accountability of village funds and government performance in Singopadu Village - Hera Lindia DivaYani; Dian Fahriani (Jurnal Mantik, 2023)
This village financial system (Siskeudes) was created by the Financial and Development Supervisory Agency (BPKP) in June 2015 in West Sulawesi. The Village Financial System (Siskeudes) has a crucial role in increasing the accountability of village funds and the performance of village governments. This research is a qualitative research which was carried out by means of independent interviews with the parties concerned regarding written information which discussed "Village Financial System Analysis (SISKEUDES) in Village Fund Accountability and Village Government Performance in Singopadu Village". This research uses a descriptive-qualitative approach so that in carrying out research to reach natural conclusions, interviews, observations and field documentation must be carried out. The location of this research is the Singopadu Village Government, Tulangan District, Sidoarjo Regency. The results of the research provide an explanation of the implementation of the Singopadu Village Government regarding the Village Financial System (SISKEUDES)